2010
DOI: 10.2134/jeq2010.0221
|View full text |Cite
|
Sign up to set email alerts
|

Nontarget Deposition and Losses of Chlorothalonil in Irrigation Runoff Water from a Commercial Foliage Plant Nursery

Abstract: Commercial foliage plant production requires the use of pesticides for controlling pests and pathogens that can reduce aesthetic qualities of crops, rendering them unwanted by consumers. Chlorothalonil is a common, broad-spectrum, foliar fungicide used for protecting plants from a variety of fungal diseases. This fungicide may also be acutely toxic to nontarget aquatic organisms due to its mode of action. This study evaluated the amount of chlorothalonil deposited on nontarget ground surfaces during normal spr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…Although the volume of water and application efficiency are vitally important to conserving water, water quality experts are also concerned about the presence of pathogens and agrichemicals in irrigation runoff from these same operations (Raudales, Parke, Guy, & Fisher, 2014;White, 2013b;Wilson, Riiska, & Albano, 2010). For example, in the U.S. there is a concern that contaminated water could impact plant communities in areas such as the Florida Everglades, the Chesapeake Bay watershed, the Great Lakes Basin, and the San Francisco Bay (White, 2013a;Wilson & Boman, 2011;Wilson & Foos, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Although the volume of water and application efficiency are vitally important to conserving water, water quality experts are also concerned about the presence of pathogens and agrichemicals in irrigation runoff from these same operations (Raudales, Parke, Guy, & Fisher, 2014;White, 2013b;Wilson, Riiska, & Albano, 2010). For example, in the U.S. there is a concern that contaminated water could impact plant communities in areas such as the Florida Everglades, the Chesapeake Bay watershed, the Great Lakes Basin, and the San Francisco Bay (White, 2013a;Wilson & Boman, 2011;Wilson & Foos, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Influent concentrations of some pesticides, nitrate, and phosphorus are an order of magnitude lower than those found in other studies of nursery runoff in bedding plant nurseries (Briggs, Whitwell, & Riley, ; White, Taylor, Chandler, Whitwell, & Klaine, ; Wilson et al., ) (Tables and ).…”
Section: Resultsmentioning
confidence: 57%
“…Pesticide concentrations in pot leachate can be toxic to aquatic organisms (Graves, Vogel, Belden, Rebek, & Simpson, ). For example, Wilson, Riiska, and Albano () found that 29% of chlorothalonil application in a nursery setting was deposited on the ground surface instead of in pots, which led to concentrations up to 500 μg L −1 in runoff, a level toxic to aquatic microorganisms (e.g., 96‐h LC 50 , the concentration that will kill half of a test population, for adult grass shrimp is 150 μg L −1 according to Key, Meyer, & Chung, ). Excess nutrients lead to algal blooms and are an ongoing challenge in both agricultural and urban runoff (Anderson, Gilbert, & Burkholder, ; Kandel, Vogel, Penn, & Brown, ; Paerl et al., ; Smith, ; Smith, King, & Williams, ; Watson et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…Bixio et al [9] argued the limited adoption of treatment technologies stems from their costs and maintenance requirements, which are prohibitive for many growers. Others [6,7,10,11] have argued that grower adoption of water treatment systems is constrained by the risks associated with phytopathogen transfer if technologies do not work consistently and efficiently. Furthermore, few studies have conducted a systematic analysis of how nursery and greenhouse growers make decisions about adopting or not adopting water treatment technologies, and what specific cognitive and social factors play a role in these processes.…”
Section: Introductionmentioning
confidence: 99%